Bargaining Chains - Lovejoy, William S. (Management Science, 2010)
We consider a firm that designs a new product and wishes to bring it to market but does not have ownership or control over all of the resources required to make that happen. The firm must select and contract with one of several possible tier 1 suppliers for necessary inputs, who do the same with their (tier 2) suppliers, etc. This general situation is common in industry. We assume tier-wise negotiations, sole sourcing within each tier, complete local information, and horizontal competition. We develop a bargaining-based solution to the negotiations between two adjacent multifirm tiers and show its consistency with familiar solution concepts from the theories of bargaining and cooperative games. We then link up multiple bargaining modules to generate chainwide predictions for efficiency and profitability in supply chains with an arbitrary number of tiers and an arbitrary number of firms per tier. We investigate the implications of the results for investments in process improvements or supplier development.